DESAIN.PEMBANGKIT.LISTRIK.TENAGA SURYA.(PLTS).MENGIKUTI.POLA.ATAP WANTILAN.DESA.ANTOSARI.UNTUK MEMENUHI.DAYA.3600.WATT - I Gusti Bagus Wiradhi Yogathama; I Wayan Arta Wijaya; I Nyoman Budiastra (Program Studi Teknik Elektro UNUD, 2021)
The design of the solar power plant (PLTS) at the Antosari village wantilan is a research thataims to realize the use of new and renewable energy which is one of the solutions inovercoming electricity needs, saving fossil energy and assisting in the realization of GovernorRegulation 45/2019 concerning Bali Clean Energy. This study carried out the design andcalculations in the design of the PLTS Atap Antosari Village. The PLTS design is carried out bypaying attention to and taking into account the tilt angle of the Helioscope Software, designingthe placement of the solar panel modules, designing the inverter, configuring the circuit, takinginto account the number of batteries used, selecting the Battery Control Unit and calculating theprofit on investment. The results of the simulation on the helioscope software are the number ofsolar modules as many as 72 units, installed at an angle of 14.95o which can supply a batterywith a capacity of 500Ah. The simulation also determines the use of an inverter that uses a 4kWinverter which produces a power of 3.6 kWp. The ability of the installed solar module to flow acurrent of 97.56A so that the full charge condition is obtained for 6 hours. Research initialcapital of Rp. 201,400,000 with a return of Rp. 1,325,376, - per month, so that the financing forinstalling PLTS will return in 2034 (13 years)